...I understand that. I swear.... Okay Dedicated, since we're all obviously not as smart as you, wanna run through that? lol

x=y, 1=1 x² = xy, 1=1 x²-y²=xy-x³, 0=0 (x+y)(x-y)=y(xy), 0=1 (Oops, problem here...) ((x+y)(x-y))/(x-y)=(y(x-y))/(x-y), 0=0 x+y=y, 2=1 (Oops, problem here...) There's something wrong here .

You almost got it right Avenger... I worked it out before: Substitute the letters for numbers 1=1 1² = 1x1 (1+1)(1-1) = 1(1-1) <----- these both = 0 (1+1)(1-1)/(1-1) = 1(1-1)/(1-1) Now, you start to cancel out... (1+1)(1-1) = 1/(1-1) Cancel out again... (1+1) = 1

Dedicated, what is the original problem. That is, before you did any work. That way I can try working it out.

The main problem is: (1+1)(1-1)/(1-1) = 1(1-1)/(1-1) or (x+y)(x-y)/(x-y) = y(x-y)/(x-y) but all you have to do is cancel it down...

But than it ends up as 2=1. Doesn't that mean it's a no solution? I mean if 2 truly equalled 1, math for me would of been hella easier.